Cosmic noise absorption during geomagnetic substorms and the possible influence of substorms on global electric circuit - Singh, A.K.; Jeeva, K.; Pathan, B.M.; Sinha, A.K.; Dhar, Ajay; Hanchinal, A.N. (My University, 2008)
The geomagnetic substorms are important consequences of solar wind-magnetosphere-ionosphere coupling. The enhanced particle precipitation in the Earth’s ionosphere during the coupling results in the enhanced absorption of the galactic cosmic radio noise. Simultaneous analysis of magnetometer and riometer data shows the enhanced absorption of cosmic noise during the substorms. The global thunderstorm activity maintains a potential difference of a few hundred kilovolt (kV) between the ionosphere and the Earth’s surface. As a result of the small but finite conductivity of the lower atmosphere, a small current of order of pico Ampere (pA) flows from the ionosphere to the Earth in the fair weather regions. Though the global electric circuit (GEC) is mainly due to global thunderstorms, physical processes such as ionospheric and magnetospheric dynamos, geomagnetic activities, solar flares, coronal mass ejections do have finite contributions towards GEC. In this paper we present simultaneous study of geomagnetic activities (monitored by DFM at Maitri), cosmic radio noise absorption (recorded by 32 MHz riometer at neighboring Russian station, Novo) and the possible influence of substorms on GEC parameters (recorded at Maitri) during year 2007.
Keywords: Geomagnetic substorms; Global electric circuit; Solar wind; Earth’s ionosphere; Coronal mass ejections